Identification of two novel mutations in three children with congenital factor VII deficiency. Issue 5 (July 2021) - Liang, Kairong; Nikuze, Lauriane; Zhang, Fuyong; Lu, Zhengjing; Wei, Manlv; Wei, Hongying
Abstract : N/A: Congenital factor VII deficiency (FVIID) is a rare F7 gene mutation causing bleeding disorder inherited in an autosomal recessive manner. In this study, we aimed to identify genetic defects and analyze their relationships with phenotype in three Chinese FVIID patients. The diagnosis of FVIID was made based on FVII coagulant activity (FVII:C) levels assessed through prothrombin time assay. Direct sequencing and protein modeling were performed to detect genetic mutations and the resulting protein expression. Patient 1, a 2-year-old girl, presented with mild bleeding and was found to have a FVII:C of 0.2% and a compound heterozygous F7 Cys389Gly/Cys115Arg mutation. Patient 2, a 7-year-old boy, consulted for moderate bleeding and was found to have a FVII:C of 0.8% and a compound heterozygous F7 Thr241Asn/Pro324Leu mutation. Patient 3, a 5-year-old boy who developed a mild bleeding after trauma was found to have a FVII:C of 1.8% and a compound heterozygous F7 Thr241Asn/ IVS5-2A>G mutation. We hereby report three congenital FVIID patients with FVII:C less than 2% and their respective F7 mutations, two of which ( F7 Cys115Arg, Pro324Leu) are novel. The molecular model analysis of the two novel mutations F7 Cys115Arg and Pro324Leu respectively indicated impairment of the proper folding of epidermal growth factor 1 domain situated on F7 gene and impairment of the procoagulant function of FVII both leading to the congenital deficiency of FVII.